2017
DOI: 10.1016/j.bbalip.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for α/β hydrolase domain 5 (ABHD5)/comparative gene identification-58 (CGI-58) at the lipid droplet interface and beyond

Abstract: Mutations in the gene encoding comparative gene identification 58 (CGI-58), also known as α β hydrolase domain-containing 5 (ABHD5), cause neutral lipid storage disorder with ichthyosis (NLSDI). This inborn error in metabolism is characterized by ectopic accumulation of triacylglycerols (TAG) within cytoplasmic lipid droplets in multiple cell types. Studies over the past decade have clearly demonstrated that CGI-58 is a potent regulator of TAG hydrolysis in the disease-relevant cell types. However, despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 112 publications
(235 reference statements)
1
17
0
Order By: Relevance
“…Further studies are in progress to define in more detail the subcellular localization of these proteins in Huh7 hepatoma cells. Overall, our studies support the notion that ABHD5 acts as a co-activator of PNPLA2 in Huh7 hepatoma cells, in a similar manner as proposed for the interaction of ABHD5 and PNPLA2 in human adipose tissue 36 .…”
Section: Role Of Abhd5 In Hepatic Triglyceride Metabolismsupporting
confidence: 88%
See 1 more Smart Citation
“…Further studies are in progress to define in more detail the subcellular localization of these proteins in Huh7 hepatoma cells. Overall, our studies support the notion that ABHD5 acts as a co-activator of PNPLA2 in Huh7 hepatoma cells, in a similar manner as proposed for the interaction of ABHD5 and PNPLA2 in human adipose tissue 36 .…”
Section: Role Of Abhd5 In Hepatic Triglyceride Metabolismsupporting
confidence: 88%
“…Abhydrolase domain containing-5 protein (ABHD5), also known as CGI-58, is a member of an esterase/thioesterase/lipase gene family. It has been implicated in having a role in triglyceride hydrolysis, as well as in TRL assembly and secretion, via activation of PNPLA2 as investigated in adipocytes and myocytes 35,36 . Liverspecific inhibition of ABHD5 in mice has shown to induce hepatic steatosis 37,38 and reduction in triglyceride hydrolase activity and TRL secretion 37 .…”
Section: Lipid-droplet Hydrolysismentioning
confidence: 99%
“…To date, several studies have demonstrated an interaction of ABHD5 with proteins involved in cellular lipid and energy metabolism ( 37 ). One of the best characterized interactions is the activation of ATGL by ABHD5 that has been identified in our laboratory ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several ATGL-independent roles for ABHD5 have also been described (Lord and Brown, 2012;Brown and Brown, 2017). For example, it has been suggested that ABHD5 has tumor suppressor functions in colorectal carcinogenesis, potentially by regulating autophagic flux and AMP-activated protein kinase signaling (Ou et al, 2014;Peng et al, 2016).…”
Section: Tablementioning
confidence: 99%